Biological Significance of Local TGF-β Activation in Liver Diseases - Hayashi, Hiromitsu; Sakai, Takao (Frontiers in Physiology, 2012)
The cytokine transforming growth factor-β (TGF-β) plays a pivotal role in a diverse range of cellular responses, including cell proliferation, apoptosis, differentiation, migration, adhesion, angiogenesis, stimulation of extracellular matrix (ECM) synthesis, and downregulation of ECM degradation. TGF-β and its receptors are ubiquitously expressed by most cell types and tissues in vivo. In intact adult tissues and organs, TGF-β is secreted in a biologically inactive (latent) form associated in a noncovalent complex with the ECM. In response to injury, local latent TGF-β complexes are converted into active TGF-β according to a tissue- and injury type-specific activation mechanism. Such a well and tightly orchestrated regulation in TGF-β activity enables an immediate, highly localized response to type-specific tissue injury. In the pathological process of liver fibrosis, TGF-β plays as a master pro-fibrogenic cytokine in promoting activation and myofibroblastic differentiation of hepatic stellate cells, a central event in liver fibrogenesis. Continuous and/or persistent TGF-β signaling induces sustained production of ECM components and of metalloproteinase synthesis. Therefore, the regulation of locally activated TGF-β levels is increasingly recognized as a therapeutic target for liver fibrogenesis. This review summarizes our present knowledge of the activation mechanisms and bioavailability of latent TGF-β in biological and pathological processes in the liver.